Molecular genetic characterization of Cryptosporidium and Cystoisospora protozoan infections in cats from large cities of Kazakhstan - Lider, Lyudmila; Uakhit, Rabiga; Manapov, Nurassyl; Yerzhanova, Valentina; Andreyev, Alexandr; Smagulova, Ainura; Hermosilla, Carlos; Kiyan, Vladimir (Frontiers in Parasitology, 2025)
IntroductionCryptosporidium spp. and Cystoisospora spp. are significant unicellular parasites that cause gastrointestinal infections in both humans and animals globally. Among these, Cryptosporidium felis and Cystoisospora felis are particularly important for feline health and pose potential zoonotic risks, especially for individuals with compromised immune systems. Kazakhstan, characterized by its diverse climate zones and an increasing population of pets, provides an excellent context for studying the epidemiology and genetic diversity of these parasites. In Kazakhstan, the mandatory registration of pets offers a valuable opportunity to explore the distribution and molecular characteristics of these parasites. This study focuses on the prevalence, genetic diversity, and zoonotic potential of Cryptosporidium and Cystoisospora from companion and shelter cats across five major cities in Kazakhstan.MethodsOverall, from five cities, 1301 fecal samples were collected and studied. Samples were study by direct modified Sheather’s flotation technique was applied using a sugar solution. Samples were screened using the 18S rRNA gene for Cryptosporidium and the ITS-1 gene for Cystoisospora. Nucleotide sequences were aligned with the MUSCLE multiple sequence alignment program. Phylograms were constructed with the MEGA11 software using the Maximum Likelihood (ML) method.Results and discussionIn total, we examined 1,301 fecal samples and found that 31 (2.4%) contained Cryptosporidium spp., including 10 identified as Cryptosporidium felis. Additionally, 121 samples (9.3%) tested positive for Cystoisospora felis. The studied Cryptosporidium parvum isolates obtained in this study belong to subtype IIdA15G1, which is dominant and clusters well with previously reported sequences from different countries on the gp60 gene. Shelter cats are more susceptible to these parasites, with a prevalence of 3.1% for Cryptosporidium and a notably higher rate of 19.0% for Cystoisospora. In contrast, companion cats showed lower rates, at 1.6% for Cryptosporidium and 5.1% for Cystoisospora. Our findings identified the species Cystoisospora felis, Cryptosporidium parvum, and Cryptosporidium felis, with a determined subtype of XIXa.